PENGARUH INFLASI DAN TINGKAT BUNGA TERHADAP INDEKS HARGA SAHAM GABUNGAN (IHSG) PADA BURSA EFEK INDONESIA - Ima Andriyani; Crystha Armereo (JURNAL MANAJEMEN DAN BISNIS SRIWIJAYA, 2016)
The unstable monetary situation as reflected in the interest rates and inflation resulting in chaos in the economy. This shows the close macroeconomics impact on stock price indices in the stock market. The purpose of this study is to assess and analyze the influence of the variables of macro-economic indicators of inflation and interest rates on stock price performance index over the period 2012 to 2014.Technique analysis in this study using multiple linear regression method using the independent variable inflation and interest rates on the Composite Index. Data obtained from the Monthly Statistic, Indonesia Stock Exchange, Economic Indicators of the Central Bureau of Statistic, Monthly Report of Bank Indonesia and the Indonesian Capital Market Directory. The result showed that the Composite Index in Indonesia Stock Exchange has a relationship but not too significant to inflationary and interest rate variables. While inflation and interest rates simultaneously affect the JCI. Simultaneously the macro variables affect inflation and interest rates of 88.4% against 11.6% JCI rest explained by other factors.